Estimation of Phenylalanine Hydroxylase Activity in Patients with Chronic Renal Failure (Indian Journal of Forensic Medicine & Toxicology, 2020)
Renal failure is a serious disease that affects the kidney and leads to different chemical changes and mostcases lead to death .The aim of the study is to measure the activity of phenylalanine hydroxyls (PAH), andbiochemical variables (urea, creatinine, and albumin) In the blood and urine of healthy and chronic renalfailure (CRF) individuals. The study included 80 patients aged between 78 and 20 years and 80 healthysubjects between the ages of 23-65 years. The results showed significant differences in the activity of PAHat P ? 0.0001 in sera and urine chronic renal failure patients compared to healthy, as the of the activitysignificantly decreased in sera of patients with CRF and increased in urine. The mean activity of PAH was54.67 ± 6.03 (IU / ml) in sera for CRF patients, whereas in healthy individuals it was 120.83 ± 23.21 (IU/ ml), and the average activity of enzyme was 61.34 ± 7.12 in urine of patients with CRF compared with33.87 ± 3.08 ( IU / ml) in healthy individuals. The activity of PAH enzyme was compared according to agegroups, showing a decrease in the age group more than 45 years more than those in the age group less than45 years with significant differences. In conclusion, the current study demonstrated that CRF is associatedwith loss of secretory function, and metabolism Endocrine actions in the kidneys, seems likely to lose renalactivity phenylalanine hydroxylase.
Keywords: Chronic renal failure, phenylalanine, phenylalanine hydroxylase, renal function tests.